Marketing Mix Analysis Regarding Customer Intention to purchase at Coffee Shop Premium - Maharani, Alyssa; Syah, Tantri Yanuar R (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the relationship between the marketing mix and purchase intention, focusing on premium coffee shops in Jakarta. The research employs the Theory of Planned Behavior (TPB) framework to assess how attitude, subjective norm, and perceived behavioral control mediate the effects of the marketing mix—product, price, place, and promotion—on consumer purchasing decisions. Data was gathered from 135 respondents, aged 15-46, who frequent coffee shops such as Starbucks Reserve and Djournal Coffee, using an online survey. The analysis was conducted through Structural Equation Modeling (SEM) using Smart PLS 4. The results indicate that the marketing mix enhances perceived customer value and shapes positive consumer attitudes towards premium coffee brands. While the marketing mix positively influences customer attitudes and subjective norms, it was found that subjective norms and perceived behavioral control do not significantly affect purchase intentions. This may be due to external factors such as market conditions and customer preferences playing a stronger role. Interestingly, value was not a direct driver of purchase intention, suggesting that cultural and social contexts, as well as personal experiences, might have a greater influence. The findings provide practical insights for premium coffee shop owners to refine their marketing strategies by focusing on enhancing the customer experience, maintaining product quality, and offering engaging promotions to encourage repeat purchases. The study contributes to the growing body of research on consumer behavior in the coffee shop industry and provides a foundation for future studies to explore additional variables influencing purchase decisions.